Bone remodeling in women with diabetes mellitus - T. P. Bardymova (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Background. 1t is known that the type 2 diabetes mellitus (DM) and osteoporosis are more often diagnosed in senior women. The condition of a bone tissue is accompanied by the metabolic violations that are typical for DM. The recent researches established the multidirectional changes of bone remodeling markers in women with type 2 DM at different age periods. Aims: to study the condition of bone remodeling in women with type 2 DM at different age periods. Materials and methods. We examined 27 women with type 2 DM, among them 15 were in the post-menopausal period and 12 with preserved menstrual function. Levels of osteocalcin, N-terminal propeptide of type 1 collagen (P1NP), C-terminal telopeptide of type 1 collagen (β-Crosslaps), 25-OH vitamin D, the ionized calcium were researched. Results. The analysis showed that increase in β-Crosslaps levels, P1NP, levels of osteocaltcin were observed in women with type 2 DM in the post-menopausal period, compared to parameters of women with type 2 DM with preserved menstrual function. Inverse correlation relation of osteocaltcin and 25-OH vitamin D was revealed in women with type 2 DM. Conclusion. Significant increase in markers of osteosynthesis and osteoresorption in women with type 2 DM was shown in the post-menopausal period compared with indicators of women with type 2 DM with preserved menstrual function.